Hemosporidian blood parasites in seabirds - a comparative genetic study of species from Antarctic to tropical habitats - Quillfeldt, Petra; Martínez, Javier; Hennicke, Janos; Ludynia, Katrin; Gladbach, Anja; Masello, Juan F.; Riou, Samuel; Merino, Santiago (Naturwissenschaften, 2010)
Whereas some bird species are heavily affected by blood parasites in the wild, others reportedly are not. Seabirds, in particular, are often free from blood parasites, even in the presence of potential vectors. By means of polymerase chain reaction, we amplified a DNA fragment from the cytochrome b gene to detect parasites of the genera Plasmodium, Leucocytozoon, and Haemoproteus in 14 seabird species, ranging from Antarctica to the tropical Indian Ocean. We did not detect parasites in 11 of these species, including one Antarctic, four subantarctic, two temperate, and four tropical species. On the other hand, two subantarctic species, thin-billed prions Pachyptila belcheri and dolphin gulls Larus scoresbii, were found infected. One of 28 thin-billed prions had a Plasmodium infection whose DNA sequence was identical to lineage P22 of Plasmodium relictum, and one of 20 dolphin gulls was infected with a Haemoproteus lineage which appears phylogenetically clustered with parasites species isolated from passeriform birds such as Haemoproteus lanii, Haemoproteus magnus, Haemoproteus fringillae, Haemoproteus sylvae, Haemoproteus payevskyi, and Haemoproteus belopolskyi. In addition, we found a high parasite prevalence in a single tropical species, the Christmas Island frigatebird Fregata andrewsi, where 56% of sampled adults were infected with Haemoproteus. The latter formed a monophyletic group that includes a Haemoproteus line from Eastern Asian black-tailed gulls Larus crassirostris. Our results are in agreement with those showing that (a) seabirds are poor in hemosporidians and (b) latitude could be a determining factor to predict the presence of hemosporidians in birds. However, further studies should explore the relative importance of extrinsic and intrinsic factors on parasite prevalence, in particular using phylogenetically controlled comparative analyses, systematic sampling and screening of vectors, and within-species comparisons.